Quantitative Analysis of the Fault-Tolerance of Pragmatic General Multicast (PGM) and Elastic Reliable Multicast (ERM) Protocols - Akpojaro, Jackson; Okonkwo, Raphael O.; Achuenu, Anthony (Discoveries in Agriculture and Food Sciences, 2017)
Multicast communication protocols are not immune from failures as a result of packets being dropped due to a broken link or time out processes. Therefore, it is essential to understand how these failures can affect the overall performance of multicast protocols over the Internet. This paper compares the fault-tolerance effect of two reliable multicast protocols: pragmatic general multicast (PGM) and elastic reliable multicast (ERM) in a situation where a multicast-aware node fails and the sub-nodes will have to request a repaired packet. A simulation model is developed in such a way that faults are randomly created on nodes and link for a specified period of time and the fault-tolerance effect on the two multicast protocols is analyzed. The model developed for this paper repeats the simulation for different network size, the results obtained show that the ERM protocol is better than the PGM as the size of the network increases. This finding is key while considering the improvement (or upgrade) of existing multicast protocols. The result is also significant at the early stage of designing new multicast protocols as it provides useful information in allocating scarce resource that can be appropriated to improve other infrastructure in the network.